2018
DOI: 10.5513/jcea01/19.4.2363
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding change on nutrients and minerals composition of goat’s milk

Abstract: The aim of this study was to analyse the effect of change of feeding realised by beginning of grazing on composition of goat milk at ecological farm RD Pod Skalkou, Tvrdošín from middle April to end of June in 150 goats in different parities. For indoor feeding meadow hay (ad libitum) with grain feed and protein concentrate was used. Outdoor feeding using pasture and the same feed mixture like in indoor feeding was realised (0.2 kg crimped oat + 0.3 kg mixture of barley and corn in ratio 2:1 and 0.1 kg protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…In the present study, the chemical composition of the milk from the Ionica goats is comparable to that reported by Di Trana et al [30], who carried out a comparative study on milk chemical and fatty acid composition in four goat breeds commonly reared in South Italy regions. Our findings, in terms of milk chemical composition, fall within the range values recorded by Rolinec et al [52] in goats raised in conditions very close to ours, i.e., grazing on pasture and supplemented with a commercial pelleted feed at housing.…”
Section: Chemical and Fatty Acid Composition Of Goat Milksupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the chemical composition of the milk from the Ionica goats is comparable to that reported by Di Trana et al [30], who carried out a comparative study on milk chemical and fatty acid composition in four goat breeds commonly reared in South Italy regions. Our findings, in terms of milk chemical composition, fall within the range values recorded by Rolinec et al [52] in goats raised in conditions very close to ours, i.e., grazing on pasture and supplemented with a commercial pelleted feed at housing.…”
Section: Chemical and Fatty Acid Composition Of Goat Milksupporting
confidence: 92%
“…The distribution of short-, medium-and long-chain FA is quite different from that reported by Cossignani et al [58], especially with regards to the amount of SMCFA and SLCFA, which were 27.7% and 35.8%, respectively, in comparison with the average of 46.8% and 8.5% found in our study. The differences in the FA profile of milk may be attributable to the goat genotype, stage of lactation, feeding regimen or to individual factors [52][53][54]. SSCFA: saturated fatty acids from C4:0 to C8:0; SMCFA: saturated fatty acids from C10:0 to C17:0; SLCFA: saturated fatty acids from C18:0 to C24:0.…”
Section: Chemical and Fatty Acid Composition Of Goat Milkmentioning
confidence: 99%
“…According to Goetsch et al [2], who explained that the concentration of lactose in milk as well as the content of fat and proteins, can be affected by the months of milking. By Rolinec et al [60] an average content of lactose present in goat's milk is 4.73%. The quality of goat milk fat and also protein is an important factor because it defines the ability of milk to be processed and has a relevant role in the nutritional and sensory quality of the products obtained from it [61].…”
Section: Discussionmentioning
confidence: 96%
“…Barlowska et al [ 5 ] and Michlová et al [ 7 ] reported seasonal effects on mineral element content in goat milk. Similarly, Pavlata et al [ 29 ] and Rolinec et al [ 30 ] reported the effect of season and lactation stage effects on Cu and Zn concentrations in goat milk. They analyzed the highest concentration of Cu, Fe, and Zn in goat milk derived from goats which were seven days on pasture.…”
Section: Discussionmentioning
confidence: 92%
“…Those mineral amounts were higher than those detected in goat milk derived from indoor feeding goats. The start of grazing of dairy goats affects the nutritive and mineral composition of goat milk [ 30 ].…”
Section: Discussionmentioning
confidence: 99%